Virtual Smart School: A Blended Learning Approach for Schools in Papua’s 3T Regions - Sampebua, Mingsep Rante; Supiyanto, Supiyanto; Kmurawak, Remuz Maurenz (Jurnal Nasional Pendidikan Teknik Informatika: JANAPATI, 2025)
Traditional classroom-based teaching methods are still used in schools, particularly in Papua’s 3T (frontier, outermost, undeveloped) areas. This highly relies on the teacher-centered method and limits the completion of the curriculum due to time constraints imposed by the schedule. This research aims to design a web-based virtual smart school as a blended learning solution for schools in Papua’s 3T areas. The virtual smart school learning media application is developed using the ADDIE model, a five-step process encompassing analysis, design, development, implementation, and evaluation. This research results in a virtual smart school application that can increase student motivation, enable independent learning, evaluate student learning progress, provide quick access to learning materials, and facilitate interactions between teachers and students at any time or location. The research concludes that virtual smart schools can become a blended learning solution to improve the quality and equity of education in underdeveloped areas of Papua.